New and future developments in microbial biotechnology and bioengineering : from cellulose to cellulase. Strategies to improve biofuel production /: from cellulose to cellulase. Strategies to improve biofuel production. (2019) - Srivastava, Neha; Srivastava, Manish; Mishra, P. K; Ramteke, P. W; Singh, Ram Lakhan
No abstract available